Prevalence and Risk Factors for Spasticity After Stroke: A Systematic Review and Meta-Analysis - Zeng, Huangling; Chen, Jian; Guo, Yang; Tan, Sheng (Frontiers in Neurology, 2021)
Background: Spasticity is a common sequela of stroke. The incidence of poststroke spasticity (PSS) has not been systematically reviewed in recent years, and some risk factors remain debated. This systematic review and meta-analysis was conducted to determine the prevalence and risk factors for PSS. Methods: We searched electronic databases (PubMed, Embase, Cochrane Library, CNKI, WANFANG and CBM) inception to May 12, 2020. Observational studies summarizing the incidence or risk factors for PSS were included. Only cohort studies were enrolled in meta-analysis. For risk factors examined in at least three different studies, we combined effects into odds ratios (OR) and 95% confidence intervals (CI). Results: One thousand four hundred sixty-seven studies were retrieved and 23 were involved in meta-analysis. The pooled prevalence of spasticity after stroke was 25.3% and that after the first-ever stroke was 26.7%. The incidence of spasticity after the first-ever stroke with paresis was 39.5%. The prevalence of disabling or severe spasticity (MAS ≥ 3) in stroke patients with paresis was 9.4% (95% CI 0.056–0.133), and severe spasticity was 10.3% (95% CI 0.058–0.149). Moderate to severe paresis (OR = 6.573, 95% CI 2.579–16.755, I2 = 0.0%), hemorrhagic stroke (OR = 1.879, 95% CI 1.418–2.490, I2 = 27.3%) and sensory disorder were risk factors for PSS. Conclusions: The incidence of PSS was significantly higher in stroke patients with paresis. Patients with moderate to severe paresis and sensory disorder should be closely followed up. The role of hemorrhagic stroke in predicting PSS remains to be further explored.